Pengaruh Pendidikan, Pengangguran dan Jumlah Penduduk Terhadap Tingkat Kemiskinan di Indonesia - Ainil Zaqiah; Mike Triani; Isra Yeni (Universitas Negeri Padang, 2023)
This study aims to know ; (1) the effect of education on the level of poverty in Indonesia; (2) the effect of unemployment on the poverty rate in Indonesia; (3) the effect of population on the poverty rate in Indonesia. This research is of a descriptive andassociative type. The data used is secondary data from 2016 to 2021 obtained fromrelated institutions. This study used panel data regression with the selected model, namely Random Effect Models, which was assisted by the Eviews 9 softwer, to find out how independent variables affect dependent variables. The results of this study show that simultaneously education, unemployment and population growth simultaneously have a significant effect on poverty in Indonesia. Furthermore, partially (1) education has a negative and significant effect on the level of poverty in Indonesia; (2) unemployment has a positive and significant effect on the poverty rate in Indonesia; (3) the population has a negative and insignificant effect on the poverty rate in Indonesia. In the future, the government must pay attention to the condition of the community to help in improving community welfare such as increasing human capital and human resources because it is one of the foundations for smooth development to reduce the level of poverty in Indonesia.